Anxiety sensitivity and intentional avoidance of physical activity in women with probable migraine. (October 2019) - Farris, Samantha G; Thomas, J Graham; Abrantes, Ana M; Lipton, Richard B; Burr, Emily K; Godley, Frederick A; Roth, Julie L; Pavlovic, Jelena M; Bond, Dale S
Introduction: Avoidance of physical activity is a common migraine management strategy. Anxiety sensitivity (i.e. fear of anxiety and bodily sensations due to physical, cognitive, or social consequences) is a potential correlate of physical activity avoidance and may strengthen beliefs about physical activity's detrimental effect on migraine. Method: Women (n = 100) with probable migraine diagnosis completed an online survey about migraine and physical activity, which included the Anxiety Sensitivity Index-3. Results: Anxiety sensitivity was associated with significantly increased odds of avoiding moderate- and vigorous-intensity physical activity. Anxiety sensitivity, particularly cognitive concerns, was associated with more frequent vigorous and moderate physical activity avoidance. Social concerns about anxiety sensitivity were associated with stronger expected likelihood of vigorous-intensity physical activity as a triggering and worsening factor in migraine. Discussion: Preliminary findings indicate that anxiety sensitivity may contribute to avoidance of moderate and vigorous physical activity and fear-based cognitions about exercise.